2019
DOI: 10.1007/s11842-019-09414-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Future Market Potential of Timber from Small-Scale Tree Farmers: Perspectives from the Southern Highlands in Tanzania

Abstract: In the rapidly growing Tanzanian economy, increasing demand for timber and limited wood supply from industrial plantations and natural forests have opened a new livelihood opportunity for smallholder farmers in the Southern Highlands of Tanzania, which is undergoing a tree-growing boom. In the absence of support services, research and statistics, the magnitude of the phenomena has remained unclear, along with the farmers' capability to meet market demands, access the markets, and negotiate prices. Primary qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…In Vietnam, the role of strong promotional policies and land allocation created a 'push effect' and induced tree growing before the demand and markets were developed (Meyfroidt and Lambin, 2008b;Sikor, 2006Sikor, , 2001, but policy measures targeted for industry development were apparently timed accordingly (Smith et al, 2017) and industrial demand was quickly established. In Tanzania, regulation increasing timber prices for government plantation wood (2007) seems to have added weight to the expansion of smallholder tree growing (Arvola et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vietnam, the role of strong promotional policies and land allocation created a 'push effect' and induced tree growing before the demand and markets were developed (Meyfroidt and Lambin, 2008b;Sikor, 2006Sikor, , 2001, but policy measures targeted for industry development were apparently timed accordingly (Smith et al, 2017) and industrial demand was quickly established. In Tanzania, regulation increasing timber prices for government plantation wood (2007) seems to have added weight to the expansion of smallholder tree growing (Arvola et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania and Uganda, demand originates from industries serving primarily domestic markets (Arvola et al, 2019;EU-FLEGT Facility, 2014). In light of the massive wood exports from Laos to Vietnam throughout the last decades (Saunders, 2014;Smirnov, 2015) and increasing wood exports to China, it is surprising how little this is reflected in smallholders' tree growing interests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plantation and cultivation of wild forest plants are suggested as a way to relieve pressure on natural forests (Jamnadass et al 2009;Malkamäki et al 2018;Arvola et al 2019). Large-scale commercial plantations and smallholder plantations are considered in publications, and studies show both negative and positive implications for socioeconomic sustainability.…”
Section: Traditional Forestry (Management For Extractive Resources)mentioning
confidence: 99%
“…Plantations of species such as pine and eucalyptus, which should have improved livelihoods, have done more harm than good due to forest conversion and the detrimental consequences for soil resources | 35 (Mwanukuzi 2009). The increasing need for timber may, on the other hand, open new opportunities for small-scale tree farmers, as Arvola et al (2019) showed in Tanzania, even though the farmers' capacity to market their wood and negotiate prices was unclear. While unhealthy competition can occur in informal markets, formalization risks less powerful actors being excluded for performing an activity that has become illegal or for being financially unable to legalize their activity (e.g.…”
Section: Traditional Forestry (Management For Extractive Resources)mentioning
confidence: 99%